Attenuation of lipopolysaccharide (LPS)-induced cytotoxicity by tocopherols and tocotrienols() - Nishio, Keiko (Elsevier, 2013)
Lipopolysaccharide (LPS) induces host inflammatory responses and tissue injury and has been implicated in the pathogenesis of various age-related diseases such as acute respiratory distress syndrome, vascular diseases, and periodontal disease. Antioxidants, particularly vitamin E, have been shown to suppress oxidative stress induced by LPS, but the previous studies with different vitamin E isoforms gave inconsistent results. In the present study, the protective effects of α- and γ-tocopherols and α- and γ-tocotrienols on the oxidative stress induced by LPS against human lung carcinoma A549 cells were studied. They suppressed intracellular reactive oxygen formation, lipid peroxidation, induction of inflammatory mediator cytokines, and cell death. Tocopherols were incorporated into cultured cells much slower than tocotrienols but could suppress LPS-induced oxidative stress at much lower intracellular concentration than tocotrienols. Considering the bioavailability, it was concluded that α-tocopherol may exhibit the highest protective capacity among the vitamin E isoforms against LPS-induced oxidative stress.